Penelitian Deskriptif dalam Pendidikan - Erwinda Rahim Tanjung; Meyniar Albina (STIKes Ibnu Sina Ajibarang, 2025)
Descriptive research in the field of education is a study that aims to provide a detailed description of various problems in the world of education, both from technical and non-technical aspects. The main objective of this study is to examine the basic principles of descriptive research in the field of education. The method used is a qualitative approach with a literature study design, where researchers examine various relevant sources such as books, scientific journals, research reports, and other references related to the topic. The findings of this study indicate that descriptive research plays an important role in describing the real conditions that occur in the world of education. This approach allows researchers to recognize, describe, and analyze various elements that influence the process and outcomes of education. Information generated from descriptive research can be used by educators, policy makers, and other related parties in developing educational strategies that are more targeted and in accordance with the needs of students.